Nitrification of Aspartate by Aspergillus flavus - Hatcher, H. J. (1971)
Heterotrophic conversion of l-aspartic acid to nitrification products by Aspergillus flavus was studied in a replacement incubation system. Numerous amino acids supported nitrification; aspartate and glutamate were about equivalent as the best sources of nitrate. Addition of sodium bicarbonate to the incubation system substantially enhanced nitrate formation for all nitrifiable amino acids except aspartic acid, but the basis for the bicarbonate effect is obscure. The yield of nitrate from l-aspartate was not approached by forms of aspartic acid resulting from substitution on the beta carbon, the amino nitrogen, or the gamma carboxyl group or by aspartate presented as the d-configuration. There was no relationship between nitrate formation and the occurrence of such possible intermediates as nitrite, bound hydroxylamine, ammonia, aspergillic acid, and beta-nitropropionic acid. Uniformly labeled (14)C-l-aspartate that was nitrified in replacement incubation led to no accumulation of label in possible nitrification products in the culture filtrate. Label was found in components of the mycelium after acid hydrolysis, with heaviest accumulation in what appeared to be glucosamine and an unidentified compound, possibly acetylglucosamine. Detectable label was redistributed into serine, glycine, and threonine.